(untitled) (Journal of the College of Basic Education, 2020)
The aim of the study is to investigate the effect of using storytime technique on developing Reading skills of Iraqi EFL Primary Pupils. The Population of this study EFL fourth-grade primary school pupils during the academic year 2018-2019. The Sample includes 68 students who were chosen randomly. The participants were divided into two groups; experiment group consisted of (35) students who were taught reading texts by using storytime technique while the control group consisted of (33) students who were taught reading skills by using traditional methods. The researcher constructed two tools to achieve the aim of the study, the first tool, a checklist to test students’ Motivation to learn English and the achievement test for students reading comprehension. The tests have been given to a group of jury members to ensure their validity and reliability, after that the tests are given to the pilot sample which consisted of (28) students. The motivation question was used before starting the experiment for the purpose of equalization and the end to test students’ motivation. The achievement test was administered upon the subjects who were invalid in the experiment. The researcher did the equalization between the experiment and control groups; in the following variables: (students’ age, intelligence quotient test score, a pre-test of motivation, students’ scores in English and gender variable). The experiment started at the 20th. Feb.2018 and ended at the 20th. Apr.2018, the researcher herself taught the two groups. The data obtained were analyzed by using t-test formula for two independent samples. The results showed that the storytime technique was effective in improving reading skills’ achievement and motivation to learn English.